Analisis Bibliometrik Peran Perawat dalam Pencegahan Stunting - Muhjalil, Rohmayanti (Jurnal Vokasi Keperawatan (JVK), 2023)
During the COVID-19 pandemic in Indonesia, the handling of stunting was hampered.The role of the nurse is needed in preventing stunting, namely as an educator, namely in efforts to promote health.The purpose of this study was to analyze the scope of research on stunting management in Indonesia during the COVID-19 pandemic using a bibliometric review process with vosviewer. Data obtained from various journals in Indonesia. The reference manager application used is Harzing's Publish and Perish to obtain bibliometric records from each research that will be used. It also used data from the Google Scholar database. Data mapping uses a digital mapping application, namely VOSviewer, data is inputted into the VOSviewer application which will then be converted into an interconnected data map. The search process is based on topic areas with titles, keywords, and abstracts related to the theme. A total of 200 relevant articles were found, but only 82 articles matched the theme. The results of the study show that the topic of the role of nurses in handling stunting in Indonesia is the most widely researched in 2021. The term "Indonesia, covid, pandemic, and role" is the most discussed topic. Through the analysis results from VOSviewer it is known that not many articles have been published with the keywords malnutrition, child, prevalence, health, nutrition status related to the topic area. This review can provide a reference for further research topics related to the role of nurses in handling stunting during the COVID-19 pandemic.